Hydrogel‐based Delivery of rhBMP‐2 Improves Healing of Large Bone Defects Compared With Autograft. Issue 9 (September 2015) - Krishnan, Laxminarayanan; Priddy, Lauren B.; Esancy, Camden; Li, Mon‐Tzu Alice; Stevens, Hazel Y.; Jiang, Xi; Tran, Lisa; Rowe, David W.; Guldberg, Robert E.
Abstract: Background: Autologous bone grafting remains the gold standard in the treatment of large bone defects but is limited by tissue availability and donor site morbidity. Recombinant human bone morphogenetic protein‐2 (rhBMP‐2), delivered with a collagen sponge, is clinically used to treat large bone defects and complications such as delayed healing or nonunion. For the same dose of rhBMP‐2, we have shown that a hybrid nanofiber mesh‐alginate (NMA‐rhBMP‐2) delivery system provides longer‐term release and increases functional bone regeneration in critically sized rat femoral bone defects compared with a collagen sponge. However, no comparisons of healing efficiencies have been made thus far between this hybrid delivery system and the gold standard of using autograft. Questions/purposes: We compared the efficacy of the NMA‐rhBMP‐2 hybrid delivery system to morselized autograft and hypothesized that the functional regeneration of large bone defects observed with sustained BMP delivery would be at least comparable to autograft treatment as measured by total bone volume and ex vivo mechanical properties. Methods: Bilateral critically sized femoral bone defects in rats were treated with either live autograft or with the NMA‐rhBMP‐2 hybrid delivery system such that each animal received one treatment per leg. Healing was monitored by radiography and histology at 2, 4, 8, and 12 weeks. Defects were evaluated for bone formation by longitudinal micro‐CT scans over 12 weeks (n = 14 per group). The bone volume, bone density, and the total new bone formed beyond 2 weeks within the defect were calculated from micro‐CT reconstructions and values compared for the 2‐, 4‐, 8‐, and 12‐week scans within and across the two treatment groups. Two animals were used for bone labeling with subcutaneously injected dyes at 4, 8, and 12 weeks followed by histology at 12 weeks to identify incremental new bone formation. Functional recovery was measured by ex vivo biomechanical testing (n = 9 per group). Maximum torque and torsional stiffness calculated from torsion testing of the femurs at 12 weeks were compared between the two groups. Results: The NMA‐rhBMP‐2 hybrid delivery system resulted in greater bone formation and improved biomechanical properties compared with autograft at 12 weeks. Comparing new bone volume within each group, the NMA‐rhBMP‐2‐treated group had higher volume (p < 0.001) at 12 weeks (72.59 ± 18.34 mm 3 ) compared with 8 weeks (54.90 ± 16.14) and 4 weeks (14.22 ± 9.59). The new bone volume was also higher at 8 weeks compared with 4 weeks (p < 0.001). The autograft group showed higher (p < 0.05) new bone volume at 8 weeks (11.19 ± 8.59 mm 3 ) and 12 weeks (14.64 ± 10.36) compared with 4 weeks (5.15 ± 4.90). Between groups, the NMA‐rhBMP‐2‐treated group had higher (p < 0.001) new bone volume than the autograft group at both 8 and 12 weeks. Local mineralized matrix density in the NMA‐rhBMP‐2‐treated group was lower than that of the autograft group at all time points (p < 0.001). Presence of nuclei within the lacunae of the autograft and early appositional bone formation seen in representative histology sections suggested that the bone grafts remained viable and were functionally engrafted within the defect. The bone label distribution from representative sections also revealed more diffuse mineralization in the defect in the NMA‐rhBMP‐2‐treated group, whereas more localized distribution of new mineral was seen at the edges of the graft pieces in the autograft group. The NMA‐rhBMP‐2‐treated group also revealed higher torsional stiffness (0.042 ± 0.019 versus 0.020 ± 0.022 N‐m/°; p = 0.037) and higher maximum torque (0.270 ± 0.108 versus 0.125 ± 0.137 N‐m; p = 0.024) compared with autograft. Conclusions: The NMA‐rhBMP‐2 hybrid delivery system improved bone formation and restoration of biomechanical function of rat segmental bone defects compared with autograft treatment. Clinical Relevance: Delivery systems that allow prolonged availability of BMP may provide an effective clinical alternative to autograft treatment for repair of segmental bone defects. Future studies in a large animal model comparing mixed cortical‐trabecular autograft and the NMA‐rhBMP‐2 hybrid delivery system are the next step toward clinical translation of this approach.